2021
DOI: 10.1186/s12884-021-03545-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal alcohol use, adverse neonatal outcomes and pregnancy complications in British Columbia, Canada: a population-based study

Abstract: Background The current study aimed to estimate the prevalence of alcohol use identified as a risk factor during pregnancies by the antenatal care providers, resulting in live births in British Columbia (BC) and to examine associations between alcohol use, adverse neonatal outcomes, and pregnancy complications. Methods This population-based cross-sectional study utilized linked obstetrical and neonatal records within the BC Perinatal Data Registry (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Second, we did not assess passive smoking or secondhand exposure, which may also affect the fetus [ 39 ]. Furthermore, we did not take into account certain factors that could be confounding, such as alcohol or cannabis use [ 40 , 41 ]. Information regarding other factors, such as comorbidities or concomitant medication use were not available and therefore were also not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not assess passive smoking or secondhand exposure, which may also affect the fetus [ 39 ]. Furthermore, we did not take into account certain factors that could be confounding, such as alcohol or cannabis use [ 40 , 41 ]. Information regarding other factors, such as comorbidities or concomitant medication use were not available and therefore were also not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Congruent with the theme of drinking due to stress, women who drink in pregnancy report more mental health problems and a greater incidence of abuse/violence compared to women who do not drink [ 21 , 32 ]. Not surprisingly, this review found that pre‐existing substance abuse/dependence problems influenced alcohol consumption in pregnant women (as they do in other groups), again highlighting the importance of early screening and addiction treatment for women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…These risk and protective factors may be useful in identifying pregnant women who may need extra screening or access to brief interventions during pregnancy. For example, it has been shown that age cohorts and education levels affect alcohol use behaviour during pregnancy, though these effects vary based on country and subpopulation [ 23 , 32 ]. For example, one study from Australia reported that being older and more educated are associated with a greater likelihood of alcohol use during pregnancy in the general population [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are myriad factors that both directly and indirectly influence why a pregnant woman may consume alcohol, many of which parallel the social determinants of health (SDHs; Government of Canada, 2020 ). Experiences of trauma ( Bhengu et al, 2019 ); stressful life events ( Edwards et al, 2019 ); intimate partner violence ( Deutsch, 2019 ); having a partner who uses substances ( Ortega-García et al, 2020 ); lower levels of education ( May et al, 2020 ); less or later access of prenatal health care ( May et al, 2020 ; Popova et al, 2021 ); and mental health challenges ( Hyer et al, 2020 ; Popova et al, 2021 ) have all been associated with an increased risk of alcohol use during pregnancy. Many pregnancies are unplanned, and not all women recognize their pregnancy during the early stages.…”
Section: Complexities Of Fetal Alcohol Spectrum Disordermentioning
confidence: 99%